A reappraisal of the roles and relationships of neighbourhood watches: an investigation of selected neighbourhood watches in the Athlone and Annenberg areas in Cape Town - Davis, Brandon (Department of Public Law, 2025)
The Neighbourhood Watch (NW) is a pervasive phenomenon that has gained footholds in many countries around the world. South Africa is no exception and, in the case of Cape Town in the Western Cape Province, they have proven to be a popular choice among the members of civil society as a method of dealing with crime. In the Cape Flats region of Cape Town, conventional state policing agencies (namely SAPS) have failed to deal with the high rates of crime – one of the reasons for the popularity of NWs. Civil policing structures are by no means a new phenomenon in South Africa, and the concept of the NW has been in existence for decades, yet not much academic research has focused on their evolution over the years – particularly those that exist in the Cape Flats region. Using a nodal governance framework, specifically that of nodal policing, this dissertation explores the evolution of their roles, and the relationships or networks they formed (or lack thereof) over time in the battle to reduce crime and to create safe and secure communities. Indeed, numerous studies have been conducted on policing in South Africa for many decades, and some have focused on non-state policing structures in the country. In doing so, they have briefly discussed NWs, however there are few comprehensive studies that have focused solely on the NW and discussed how they have evolved over time. This study addresses that particular gap in the literature. A qualitative study was conducted and members of three different NWs on the Cape Flats located in different areas (two from the Athlone precinct and one from the Manenberg precinct) were interviewed in three separate focus group interviews. The NWs selected for this study were the Bridgetown and Silvertown NWs (Athlone precinct) and the Surrey Estate NW (Manenberg precinct). Importantly, a precinct is a defined district or region of a city which consists of multiple areas (South African National Treasury, 2014:np).